Understanding Mozambique's growth experience through an employment lens - Sam Jones; Finn Tarp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
Over the past twenty years, Mozambique has achieved remarkable progress in promoting macroeconomic growth and stability. Nonetheless, poverty rates remain high and labour market activity is dominated by smallholder farming. We use recent household survey data to dig into these trends and provide an updated analysis of transformation in the labour market. We find that movement of labour out of agriculture has contributed to aggregate growth. But, this trend is slowing and is leading to a saturation of the services sector. Moreover, productivity growth is weakening within more labour-intensive sectors. We conclude by reflecting on policy challenges, including demographic trends.
Keywords: O11; O40; O55; J11; 330; Mozambique; labour productivity; structural transformation; poverty; growth